2018
DOI: 10.7554/elife.35957
|View full text |Cite
|
Sign up to set email alerts
|

Functional trade-offs and environmental variation shaped ancient trajectories in the evolution of dim-light vision

Abstract: Trade-offs between protein stability and activity can restrict access to evolutionary trajectories, but widespread epistasis may facilitate indirect routes to adaptation. This may be enhanced by natural environmental variation, but in multicellular organisms this process is poorly understood. We investigated a paradoxical trajectory taken during the evolution of tetrapod dim-light vision, where in the rod visual pigment rhodopsin, E122 was fixed 350 million years ago, a residue associated with increased active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 137 publications
(371 reference statements)
1
36
0
Order By: Relevance
“…( B ) Retinal release rate for bovine rhodopsin and bovine rhodopsin with substitutions matching the marine and freshwater croaker sequences at site 119, 122, 124, and 261. Marine substitutions previously published in Castiglione and Chang (2018) . ( C ) Bar chart comparing retinal release rate half-life for each pigment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( B ) Retinal release rate for bovine rhodopsin and bovine rhodopsin with substitutions matching the marine and freshwater croaker sequences at site 119, 122, 124, and 261. Marine substitutions previously published in Castiglione and Chang (2018) . ( C ) Bar chart comparing retinal release rate half-life for each pigment.…”
Section: Resultsmentioning
confidence: 99%
“…2010 ), and recovery phase of the light-activated receptor ( Hauser et al. 2017 ; Castiglione and Chang 2018 ; Gutierrez et al. 2018 ; Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Why did these substitutions serendipitously blocking SARS-CoV-2 binding only evolve in some rodent species? The compensatory interactions inherent to intramolecular epistasis can both open and close evolutionary trajectories depending on how accessible favorable mutational combinations are within evolutionary space (31,(52)(53)(54). In humans and dogs, this trajectory appears to have been closed by the presence of deep valleys containing detrimental intermediates with compromised ACE2 function (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of ACE2 enzymatic processing of Ang II to Ang-(1-7) in protection against pathogenic features of multiple cardiovascular and kidney diseases (37,41,42), it is possible that that the extant mutational combinations observed in nature (e.g. human, bat, dog, mouse, pangolin) may all represent alternative sequence 'solutions' (34,52) each uniquely required for an animal's physiology, thereby representing fitness 'peaks' in the sequence landscape (28,31,34,53,(63)(64)(65). Species variation in ACE2 hydrolysis rates we observed may reflect variation in renin activity levels, which are a major factor in determining circulating Ang-II levels in humans (39,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…We found positively selected substitutions in the lineage leading to gymnotiforms in helices that are known to undergo the largest molecular movements upon rhodopsin photoactivation [33], and where substitutions have been shown in mutagenesis studies to affect the kinetics of chromophore release by rhodopsin [43 -45]. Substitutions that affect rhodopsin kinetics are known to have evolved convergently in distantly related species inhabiting dim-light environments [46,47], including other fishes inhabiting the same rivers of the Amazon basin [37]. Interestingly, mutagenesis studies in bovine rhodopsin have also shown that the F220C substitution experimentally decreases the rate of retinal release [35].…”
Section: Discussionmentioning
confidence: 99%